Aids for people with Alzheimer's disease or other dementia I - Ang, Yu Kun (2013)
With the rise in numbers of dementia cases in Singapore and globally, there is a need to provide new ways in helping the dementia patients. Although most cases of dementia do not have treatments that can fully cure or stop the disease, it is possible to help the patients slow down the deterioration of the brain functions